2017
DOI: 10.1007/s40477-017-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic intratendinous ganglion cyst of the extensor digitorum tendon following intravenous cannulation

Abstract: Peripheral venous cannulation is one of the most commonly performed medical procedures in hospital medicine. The dorsal metacarpal veins are typically used for cannulation as they are easily accessible. We present the first case of an iatrogenic intratendinous ganglion cyst of the extensor digitorum tendon of the middle finger following intravenous cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The initial search revealed 36 records, and nine articles were included in the review ( Figure 3 ). One article was level IV evidence [ 8 ] and eight articles level V [ 1 7 , 9 ]. The same independent investigators extracted data from the studies for the final descriptive data synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search revealed 36 records, and nine articles were included in the review ( Figure 3 ). One article was level IV evidence [ 8 ] and eight articles level V [ 1 7 , 9 ]. The same independent investigators extracted data from the studies for the final descriptive data synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies, including our case, revealed 18 patients with 22 intratendinous hand ganglia ( Table 1 ) [ 1 9 ]. Women are affected more frequent than men (75% Vs 25%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations